A Passive Optical Add/Drop Multiplexer (P_OADM) For Wavelength Division Multiplexing (WDM) System - Abu Bakar, Ruzita (2001)
The revolutionary of optical networks is linked to Wavelength Division Multiplexing (WDM) to provide additional capacity on existing fibre. This creates a vision of an all-optical network where all management is carried out in the photonic layer. Optical Addl/Drop Multiplexer (OADM) is one of the important components to realize the WDM technology for optical fibre communication systems. OADM functions as the optical sub-system to facilitate the evolution of the single wavelength point-to-point optical network to the WDM networks by selectively removing and reinserting individual channels, without having to regenerate all WDM channels. This thesis presents prototyping of a novel passive OADM called as Passive Optical AddlDrop Multiplexer (P_OADM). This thesis describes the development, characterisation and analysis of P_OADM to be used in WDM system. Two types of P_OADM have been studied; a P_OADM with single channel drop system and a P_OADM with dual channel drop system. The advantages of P_OADM are lower loses, lower cost of production and easier to customise the channels to customers' demand. In this study thorough characterisation on the components has been performed prior to system development and characterisation. The most important parameters explored are functional test, insertion losses, crosstalk, return loss, and wavelength flexibility. The results testified that P_OADM could be used for WDM system by dropping and adding the intended channel. The test result showed that the P_OADM performed within the acceptable range. The insertion lost measured was at 8.28 dB for single channel input test and 10.30 dB for two channels input test. The crosstalk measured at the drop port was 19.90 dB and 20.32 dB at the output port and the return loss was 4.93 dB. The P_OADM can be improved in term of insertion loss using circulator, or combiner but with slightly higher cost.